Electrocardiographic Reference Values for a Population of Older Adults in Sub‐Saharan Africa. Issue 1 (9th September 2013) - Dewhurst, Matthew J.; Di, Luigi Y.; Dewhurst, Felicity; Adams, Philip C.; Murray, Alan; Orega, Golda P.; Mwita, Julius C.; Walker, Richard W.; Langley, Philip
<x xml:space="preserve">Abstract</x> Background/Objectives Older adults in sub‐Saharan Africa (SSA) are at greatest risk of an impending noncommunicable diseases epidemic, of which cardiac disease is the most prevalent contributor. Thus, it is essential to establish electrocardiographic reference values for a population that is likely to differ genetically and environmentally from others where reference values are established. Methods Two thousand two hundred thirty‐two apparently healthy community‐based participants without known cardiac disease aged 70+ in rural Tanzania underwent 12‐lead electrocardiography. Electrocardiograms were digitally analyzed and gender‐specific reference values for P duration (PD), P amplitude (PAMP), P area (PAREA), P terminal negative force (V1) (PTNF), PR interval, QRS duration (QRSD), QT/QTc, R amplitude (II, V5) (RAMP) LVH index (LVHI), R axis and R/S ratio (V1) reported, following univariate analysis of covariance using a multiple linear regression model, adjusting for age, systolic blood pressure (SBP), body mass index (BMI), and RR interval. Results Data from 1824 subjects were suitable for analysis. Adjusted mean values for men/women were: PD 115/110 ms, PAMP (avg) 123/114 μV, PAMP (II) 203/190 μV, PAREA (avg) 5.3/4.6 mV*s, PAREA (II) 9.3/8.1mV*s, PTNF 1.7/1.4 mV*s, PR 158/152 ms, QRSD 89/84 ms, QT 370/375 ms, QTc 421/427 ms, RAMP (II) 805/854 μV, (V5) 2022/1742 μV, LVHI 3.0/2.8 mV (Sokolow‐Lyon), 1.293/1.146 mV (Cornell), R axis 51/49°, R/S 0.2/0.2. Excluding PTNF, R axis and R/S ratio, all gender differences were significant (P < 0.001 apart from LVHI [Sokolow‐Lyon; P < 0.005)] and RAMP (II) [P < 0.05]) following adjustment for age, SBP, BMI, and RR interval. Conclusions Our description of comprehensive electrocardiographic parameters establishes reference values in this genetically and environmentally diverse SSA population thereby allowing identification of "outliers" with potential cardiac disease.